2017
DOI: 10.4049/jimmunol.1700116
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Effector Functions Due to Antibody Defucosylation Depend on the Effector Cell Fcγ Receptor Profile

Abstract: Abs of the IgG isotype are glycosylated in their Fc domain at a conserved asparagine at position 297. Removal of the core fucose of this glycan greatly increases the affinity for FcγRIII, resulting in enhanced FcγRIII-mediated effector functions. Normal plasma IgG contains ∼94% fucosylated Abs, but alloantibodies against, for example, Rhesus D (RhD) and platelet Ags frequently have reduced fucosylation that enhances their pathogenicity. The increased FcγRIII-mediated effector functions have been put to use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 45 publications
8
73
0
1
Order By: Relevance
“…However, we have previously shown that different antibodies and antigens showed similar results in erythrophagocytosis by monocyte-derived macrophages. 29 Our finding of FcgRIIIa being constitutively expressed on all red pulp macrophages is in line with several older publications showing FcgRIII in the red pulp of the spleen, but is in direct contrast with an immunohistochemistry study by Wu et al that proposed that FcgRIII is only expressed on splenic macrophages in a minority of individuals. 30 However, we consistently observed FcgRIIIa on red pulp macrophages of 82 individuals, as tested by immunofluorescence of spleen sections and flow cytometry of freshly isolated single-cell suspensions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we have previously shown that different antibodies and antigens showed similar results in erythrophagocytosis by monocyte-derived macrophages. 29 Our finding of FcgRIIIa being constitutively expressed on all red pulp macrophages is in line with several older publications showing FcgRIII in the red pulp of the spleen, but is in direct contrast with an immunohistochemistry study by Wu et al that proposed that FcgRIII is only expressed on splenic macrophages in a minority of individuals. 30 However, we consistently observed FcgRIIIa on red pulp macrophages of 82 individuals, as tested by immunofluorescence of spleen sections and flow cytometry of freshly isolated single-cell suspensions.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that, despite differences in FcgR expression levels, monocyte-derived macrophages are an equally suitable model as isolated red pulp macrophages when studying the in vitro effects of IVIg on macrophage phagocytosis. 8,29 Concluding, we describe the splenic architecture and FcgR expression on splenic macrophages both in situ and with a novel method for the specific isolation of splenic red pulp macrophages. These red pulp macrophages have an expression profile that is highly distinct from monocytes and monocytederived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 While glycan truncation may affect antibody stability, 27 defucosylation may enhance effector functions. 28 N-Glycan optimization can also be used to maximize ADCC. 29 Most intriguing, glycan may also regulate antigen recognition, and it has been reported that core fucosylation of IgG B cell receptor is required for antigen recognition and antibody production.…”
Section: Introductionmentioning
confidence: 99%
“…We observed increased IgG4‐specific Fc fucosylation in both IgG4‐RD and PSC. Non‐fucosylated IgG1 (and IgG4) antibodies bind FcγRIIIa with a 20–30‐fold higher affinity than fucosylated antibodies, and the small increase in fucosylation is in fact an almost twofold decrease in the relative amount of these non‐fucosylated antibodies . This interesting observation may suggest novel FcR binding and reduced antibody‐dependent cytotoxicity in patients with IgG4‐RD and PSC.…”
Section: Discussionmentioning
confidence: 89%